Clostridioides difficile infection with isolates of cryptic clade C-II: a genomic analysis of polymerase chain reaction ribotype 151. (April 2023) - Ducarmon, Quinten R.; van der Bruggen, Tjomme; Harmanus, Céline; Sanders, Ingrid M.J.G.; Daenen, Laura G.M.; Fluit, Ad C.; Vossen, Rolf H.A.M.; Kloet, Susan L.; Kuijper, Ed J.; Smits, Wiep Klaas
Abstract: Objectives: We report a patient case of pseudomembranous colitis associated with a monotoxin-producing Clostridioides difficile belonging to the very rarely diagnosed polymerase chain reaction (PCR) ribotype (RT) 151. To understand why this isolate was not identified using a routine commercial test, we performed a genomic analysis of RT151. Methods: Illumina short-read sequencing was performed on n = 11 RT151s from various geographical regions to study their genomic characteristics and relatedness. Subsequently, we used PacBio circular consensus sequencing to determine the complete genome sequence of isolates belonging to cryptic clades C–I and C-II, which includes the patient isolate. Results: We found that 1) RT151s are polyphyletic with isolates falling into clades 1 and cryptic clades C–I and C-II; 2) RT151 contains both nontoxigenic and toxigenic isolates and 3) RT151 C-II isolates contained monotoxin pathogenicity loci. The isolate from our patient case report contains a novel-pathogenicity loci insertion site, lacked tcdA and had a divergent tcdB sequence that might explain the failure of the diagnostic test. Discussion: This study shows that RT151 encompasses both typical and cryptic clades and provides conclusive evidence for C. difficile infection due to clade C-II isolates that was hitherto lacking. Vigilance towards C. difficile infection as a result of cryptic clade isolates is warranted.